TIME MANAGEMENT IN LEARNING ENGLISH DURING ONLINE CLASSES - Ayu Addara Putri Damanik; Anne Lou Hendriks (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2022)
Learning online or online is the right choice, to minimize the spread of the corona virus 19. The Indonesian government through the Minister of Education and Culture announced that the learning process that had been carried out face-to-face in schools had shifted to learning done from home during the Covid 19 pandemic. But at that time students are expected to be able to organize themselves and become disciplined in online learning. This paper analyzed the importance of time management in learning English during online class. Research question included (1). Is managing time well important during online learning? (2). Does managing time well affect the success of students taking online class? (3). Do students need to keep practice their English even if online learning is implemented? This study is a qualitative research design, and the questionnaires were distributed online to students from different major via google form. There were 43 respondents in this study. According to the study’s findings, 90,7% Strongly Agree that having a good time management during online learning is important and 90,7% Strongly Agree that their time management skill need more improvement.Keywords: Covid 19; Learning English; Online class; Time management